An efficient calculation method for pharmacokinetic parameters in brain permeability study using dynamic contrast‐enhanced MRI. Issue 2 (29th March 2015) - Wang, Chunhao; Yin, Fang‐Fang; Chang, Zheng
Abstract : Purpose: To develop an efficient method for calculating pharmacokinetic (PK) parameters in brain DCE‐MRI permeability studies. Methods: A linear least‐squares fitting algorithm based on a derivative expression of the two‐compartment PK model was proposed to analytically solve for the PK parameters. Noise in the expression was minimized through low‐pass filtering. Simulation studies were conducted in which the proposed method was compared with two existing methods in terms of accuracy and efficiency. Five in vivo brain studies were demonstrated for potential clinical application. Results: In the simulation studies using chosen parameter values, the calculated percent difference of K trans by the proposed method was <5.0% with a temporal resolution (Δ t ) < 5 s, and the accuracies of all parameter results were better or comparable to existing methods. When analyzed within certain parameter intensity ranges, the proposed method was more accurate than the existing methods and improved the efficiency by a factor of up to 458 for a Δ t = 1 s and up to 38 for a Δ t = 5 s. In the in vivo study, the calculated parameters using the proposed method were comparable to those using the existing methods with improved efficiencies. Conclusions: An efficient method was developed for the accurate and efficient calculation of parameters in brain DCE‐MRI permeability studies. Magn Reson Med 75:739–749, 2016. © 2015 Wiley Periodicals, Inc.